A retrospective survey of dengue fever among Japanese individuals staying in Manila, Philippines. Issue 1 (December 2016) - Hamada, Atsuo; Tada, Yuki; Fukushima, Shinji; Murata, Hidemi; Kikuchi, Hirohisa
Abstract Dengue fever is a serious concern for Japanese people staying in Southeast Asia. In order to implement necessary prophylactic measures for dengue fever in this population, we investigated the characteristics of dengue fever among Japanese nationals living in Manila, Philippines. From 2012 to 2015, 175 Japanese expatriates were diagnosed with dengue fever at the medical clinic of the Japanese Association Manila, Inc. Most of the patients were employees of Japanese companies and their families and were long-term residents of Manila. Most patients were either <10 years or in their 30s to 40s. Two patients (1.1 %) were diagnosed with dengue hemorrhagic fever. No deaths due to dengue fever were reported. The reported number of patients with dengue fever has shown a decreasing trend: from 55 cases in 2012 to 53 in 2013, 31 in 2014, and 36 in 2015. The results of this survey could be useful for the development of effective dengue fever preventive measures such as health education and provision of information among not only Japanese but also other foreigners residing in endemic areas.